2018
DOI: 10.1128/mbio.02408-18
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and Loss of CTX-M-Producing and Non-Producing Escherichia coli in the Fecal Microbiome of Travelers to South Asia

Abstract: Escherichia coli strains which produce CTX-M extended-spectrum beta-lactamases are endemic as colonizers of humans and in the environment in South Asia. This study demonstrates that acquisition of CTX-M-producing E. coli (CTX-M-EC) in travelers from the United Kingdom to South Asia is polyclonal, which is likely due to multiple acquisition events from contaminated food and drinking water during travel. CTX-M-EC frequently persists in the fecal microbiome for at least 1 year after acquisition, often alongside n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…Over the duration of their visits, the volunteers were colonized by up to five different strains, and often acquired multiple ESBL-GN species. Few traveler studies have employed genome-level analyses [18], but several have reported isolating more than one new colonizing ESBL-GN strain from posttravel samples [10][11][12][13][14]. Our data reveal the true scale and complexity at which drug-resistant bacteria colonize the intestinal tract during travel, demonstrating that it has been seriously underestimated.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Over the duration of their visits, the volunteers were colonized by up to five different strains, and often acquired multiple ESBL-GN species. Few traveler studies have employed genome-level analyses [18], but several have reported isolating more than one new colonizing ESBL-GN strain from posttravel samples [10][11][12][13][14]. Our data reveal the true scale and complexity at which drug-resistant bacteria colonize the intestinal tract during travel, demonstrating that it has been seriously underestimated.…”
Section: Discussionmentioning
confidence: 85%
“…Colonization occurs even during short visits [8][9][10][11][12][13][14][15] and without antimicrobial use [17] and can last for months or even over a year [8,12,13] and lead to further spread after return home [8,13]. Genome-level analysis of MDR strains colonizing travelers shows that newly acquired MDR strains tend to displace resident intestinal commensal E. coli strains alongside new non-MDR strains, such that the pre-travel population remains as a minority [18].…”
Section: Introductionmentioning
confidence: 99%
“…The explanation for this is not clear. The ecological fallacy could be operating as described above, or given people can become persistently colonised with resistant E. coli following a short stay in a different environment, for example during overseas travel or hospitalisation, [32,33] another possibility is that co-amoxiclav and cefalexin resistance in the community is linked to use of these or related drugs in other settings, such as secondary care. In a 2017/18 survey of 900 cefalexin resistant urinary E. coli isolates from primary care in the same study area, 626 (69.6%) were found to be resistant to third generation cephalosporins used in secondary care, of which 571 (91.2%) produced the extended spectrum beta-…”
Section: Results In the Context Of Existing Researchmentioning
confidence: 99%
“…It has also been reported that phylogroup B2 or D strains predominated (>70%) in the E. coli strains isolated from biopsy samples of human lower intestinal tracts in Australia (Gordon et al 2015). However, in a recent analysis of E. coli strains isolated from healthy individuals who traveled from the United Kingdom to South Asia (Bevan et al 2018), not only phylogroups B2 and D strains but also phylogroup A strains were predominant. In another recent study that analyzed E. coli isolates from Tanzanian children under the age of 5, phylogroups A and B1 strains were most frequently isolated (Richter et al 2018).…”
Section: Discussionmentioning
confidence: 97%